2010
DOI: 10.1007/s00244-010-9502-9
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Injury and Cellular Immune Responses to Cadmium Chloride Exposure in the Common Mussel Mytilus edulis: Modulation by Lipopolysaccharide

Abstract: The immunotoxic effects of cadmium (Cd) exposure in bivalves are poorly understood and whether or not stimulation of the immune system exacerbates Cd toxicity is unclear. The mussel Mytilus edulis was exposed to 20 or 50 μg/l total Cd for up to 11 days compared to no added Cd controls to assess immune and other physiological responses. Selected experiments were then repeated in the presence of a lipopolysaccharide (LPS) challenge with and without subsequent Cd exposure. Immune functions of hemocytes, hematolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(25 citation statements)
references
References 40 publications
1
23
1
Order By: Relevance
“…In this study, gills presented loss of frontal cilia and lateral cilia after TBBPA treatment for 30 days, which suggested that TBBPA might affect the normal respiration and nutrient uptake. Similar phenomena have been reported in mussels exposed to tri-n-butyltin, Cd and mussels from natural polluted environments polluted by various heavy metals (Micic et al, 2001;Sheir and Handy, 2010;Fasulo et al, 2008). Due to a lack of adaptive immunity in mussels, the hemocytes are very important for immune defense, and the circulating hemocytes are able to penetrate tissue in response to antigens.…”
Section: Tbbpa Induced Damages and Apoptosis In Mussel Gillssupporting
confidence: 48%
See 1 more Smart Citation
“…In this study, gills presented loss of frontal cilia and lateral cilia after TBBPA treatment for 30 days, which suggested that TBBPA might affect the normal respiration and nutrient uptake. Similar phenomena have been reported in mussels exposed to tri-n-butyltin, Cd and mussels from natural polluted environments polluted by various heavy metals (Micic et al, 2001;Sheir and Handy, 2010;Fasulo et al, 2008). Due to a lack of adaptive immunity in mussels, the hemocytes are very important for immune defense, and the circulating hemocytes are able to penetrate tissue in response to antigens.…”
Section: Tbbpa Induced Damages and Apoptosis In Mussel Gillssupporting
confidence: 48%
“…Histological sections (6-8 μm thickness) were stained with hematoxylin-eosine (HE) and observed under a light microscope (Olympus BX61, Tokyo, Japan) at × 200 magnification (zoom on the camera was × 2.5). The injury of mussel gills was measured according to previous study with some modifications (Sheir and Handy, 2010). The detailed information on making sections and histological observations were described in the Supporting Information.…”
Section: Histologymentioning
confidence: 99%
“…This mechanism can explain the stimulation of caspase-independent apoptosis in molluscan hemocytes by Cd (Sokolova et al, 2004) and may contribute to Cd-induced immunosuppression (Butler and Roesijadi, 2000;Sheir and Handy, 2010;Bruneau et al, 2013;Ivanina et al, 2014).…”
Section: Discussionmentioning
confidence: 96%
“…LPS and zymosan (Sigma) at a concentration of 300 mg/g wet weight were selected for the assay based on previous studies [52,53]. A total of 13 oysters were held in 10 L tanks with aeration.…”
Section: Short-term Exposure To Unencapsulated Immunostimulantsmentioning
confidence: 99%